Application of Molecular Vapour Deposited Al2O3 for Graphene-Based Biosensor Passivation and Improvements in Graphene Device Homogeneity - Muhammad Ali (Nanomaterials, 2021)
Graphene-based point-of-care (PoC) and chemical sensors can be fabricated using photolithographic processes at wafer-scale. However, these approaches are known to leave polymerresidues on the graphene surface, which are difficult to remove completely. In addition, graphenegrowth and transfer processes can introduce defects into the graphene layer. Both defects and resistcontamination can affect the homogeneity of graphene-based PoC sensors, leading to inconsistentdevice performance and unreliable sensing. Sensor reliability is also affected by the harsh chemicalenvironments used for chemical functionalisation of graphene PoC sensors, which can degrade partsof the sensor device. Therefore, a reliable, wafer-scale method of passivation, which isolates thegraphene from the rest of the device, protecting the less robust device features from any aggressive chemicals, must be devised. This work covers the application of molecular vapour depositiontechnology to create a dielectric passivation film that protects graphene-based biosensing devicesfrom harsh chemicals. We utilise a previously reported “healing effect” of Al2O3 on graphene toreduce photoresist residue from the graphene surface and reduce the prevalence of graphene defects to improve graphene device homogeneity. The improvement in device consistency allows formore reliable, homogeneous graphene devices, that can be fabricated at wafer-scale for sensing andbiosensing applications.